Cultural management a research overview - Bilton, Chris (Routledge, 2023)
A Very Short History of Cultural Management -- Cultural Management 1.0: managing creativity through freedom and control -- Cultural Management 2.0: managing change through cultural entrepreneurship -- Cultural Management 3.0: managing co-creation through vulnerable leadership -- Leading for Innovation: connecting theories to practice.
Keywords: Kulturmanagement / (DE-627)091373166 / (DE-2867)18923-4; Organisatorischer Wandel / (DE-627)091381894 / (DE-2867)12105-5; Führungsstil / (DE-627)091361583 / (DE-2867)15825-5; Innovationsmanagement / (DE-627)091367867 / (DE-2867)19548-6; Creative ability in business; Management